2020
DOI: 10.1055/a-1155-6468
|View full text |Cite
|
Sign up to set email alerts
|

Tränenfilmosmolarität gesunder Probanden: Vergleichbarkeit zweier Osmometer

Abstract: Zusammenfassung Hintergrund Die Hyperosmolarität des Tränenfilms gilt als bedeutendes klinisches Zeichen des trockenen Auges und als wichtigster singulärer diagnostischer Parameter. Neben dem seit einigen Jahren verfügbaren Ocusense TearLab-Osmometer (TearLab Corp, San Diego, CA) ist seit Kurzem auch das I-Pen-Osmometer (I-MED Pharma Inc., Dollard-des-Ormeaux, Quebec, Kanada) verfügbar. Das Ziel unserer Studie war die Vergleichbarkeit der mittels TearLab- und I-Pen-Osmometer erhobenen Tränenfilmosmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Tavakoli et al found that, in vivo, both instruments displayed poor repeatability (83). Some studies have found that after treatment, the osmotic pressure of tears in patients with dry eye is significantly reduced (74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86). However, other studies have found that the osmotic pressure of tears does not change significantly after treatment (84)(85)(86)(87)(88).…”
Section: I-pen Tear Osmolarity Testmentioning
confidence: 99%
“…Tavakoli et al found that, in vivo, both instruments displayed poor repeatability (83). Some studies have found that after treatment, the osmotic pressure of tears in patients with dry eye is significantly reduced (74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86). However, other studies have found that the osmotic pressure of tears does not change significantly after treatment (84)(85)(86)(87)(88).…”
Section: I-pen Tear Osmolarity Testmentioning
confidence: 99%